Can a tiered water price policy improve the technical efficiency of crop irrigation for maize in the Heihe River Basin in Northwest China? - Guifang Li; Dongdong Ma (Agricultural Water Management)
Agricultural water pricing reform is often considered one of the most effective tools for improving agricultural water use efficiency in China’s arid and semi-arid regions. However, the implementation effect of this policy remains to be studied. On the basis of farmer survey data in 2014 and 2019, this study takes typical irrigation districts in the Heihe River Basin (HRB) in Northwest China as the study area and measures the net effect of a tiered water price policy (TWPP) on the technical efficiency of crop irrigation (TECI) by constructing sub-vector data envelopment analysis (DEA) and difference-in-differences (DID) models. The results reveal that from 2014 to 2019, the average TECI for seed maize and field maize in the Plain Irrigation District (PID) increased by 0.1419 and 0.1242, respectively. Furthermore, compared with nonpilot villages, the implementation of the TWPP can significantly increase the TECI for seed maize and field maize in pilot villages by 16.24 % and 19.70 %, and this positive effect is significant at the 1 % and 5 % levels, respectively. Furthermore, for the pilot villages, the higher the water price borne by farmers is, the lower the TECI, indicating that compared with farmers who bear lower water prices, these farmers have excessive irrigation behaviour. Finally, it also found that compared with nonpilot villages, the TWPP helps seed maize and field maize via saving irrigation water in pilot villages by 27.56 % and 27.74 %, respectively.